Prevalência da violência sexual e fatores associados em acadêmicos da área da saúde da Universidade de Rio Verde: estudo transversal - Barreto, Tiago Guimarães Gomez (Universidade do Vale do Rio dos Sinos, 2023)
Sexual violence is a serious health problem, bringing cynical consequences such as physical trauma, sexually transmitted infections and unwanted pregnancies, in addition to numerous disorders related to mental health. In view of the seriousness of this problem, the present study aimed to study the prevalence of sexual violence in students in the health area and the associated factors. A standardized questionnaire was applied addressing various health issues, including sexual violence, in which 2295 students from the health area of the University of Rio Verde participated. A 7% prevalence of sexual violence was identified among university students. Sexual violence was associated with the female gender in 8.1% versus 4.5% of males, age, being more prevalent among the elderly, and excessive consumption of alcohol and other drugs. Regarding the frequency of alcohol consumption, the higher it was, the more it was associated with sexual victimization, being in 20% of harmful users. Psychological stress was also associated with sexual violence in 11.44% of those who declared themselves to be experiencing severe stress. It is concluded that sexual violence among university students in our environment was in line with findings in the literature, and it is fundamental, in the university environment, to approach this theme, focusing on preventive measures and adequate assistance to victims.
Keywords: Violência sexual; Universitários; Prevalência; Fatores associados; Sexual violence; College students; Prevalence; Associated factors; ACCNPQ::Ciências da Saúde::Saúde Coletiva